Development of newton's law physics e-book on motion based on technological pedagogical content knowledge (TPACK) - Masrifah, Masrifah; Samsudin, Achmad; Amiroh, Dewi; Costu, Bayram (UIN Sunan Gunung Djati Bandung, 2024)
The use of technology in education allows learning activities to be more varied, easy and enjoyable so that it can influence students' understanding of concepts in physics learning. Research which aims to develop an e-book on Physics of Newton's laws of motion based on Technological Pedagogical and Content Knowledge (TPACK) which is suitable for increasing students' understanding of the concept has been carried out. This development research uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Based on the results of expert validation data analysis, an average percentage value of 88% was obtained with the category suitable for use in the learning process. This is supported by the results of students' understanding of e-book’s content, which was 86.41 in the high category. Likewise, students' responses of the e-book developed show that the e-book is very good for use in the learning process to increase students' understanding of concepts and create interesting and meaningful learning.